2021
DOI: 10.1002/pon.5734
|View full text |Cite
|
Sign up to set email alerts
|

Change in cognition before and after non‐central nervous system cancer diagnosis: A population‐based cohort study

Abstract: Objective: Clinical studies showing that non-central nervous system cancer patients can develop cognitive impairment have primarily focused on patients with specific cancer types and intensive treatments. To better understand the course of cognitive function in the general population of cancer patients, we assessed cognitive trajectories of patients before and after cancer diagnosis in a population-based setting. Methods: Between 1989 and 2014, 2211 participants from the population-basedRotterdam study had bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…In non-CNS tumor patients, local therapy (surgery or radiotherapy) did not have a substantial impact on cognition [29][30][31][32][33][34]. Only for sinonasal and gynecological cancers, impaired cognitive functioning was found after radiotherapy and/or surgery [19,35].…”
Section: Neuropsychological Testingmentioning
confidence: 99%
“…In non-CNS tumor patients, local therapy (surgery or radiotherapy) did not have a substantial impact on cognition [29][30][31][32][33][34]. Only for sinonasal and gynecological cancers, impaired cognitive functioning was found after radiotherapy and/or surgery [19,35].…”
Section: Neuropsychological Testingmentioning
confidence: 99%
“…Thirty-nine studies (60%) examined cognitive functional outcomes among cancer survivors; 32 were longitudinal in design ( 77,78,81]. Six of these studies (n = 6/16; 37%) reported clinically meaningful differences between survivors and controls [22,31,42,49,70,73].…”
Section: Studies Examining Cognitive Functional Outcomes Among Cancer...mentioning
confidence: 99%
“…Six of these studies (n = 6/16; 37%) reported clinically meaningful differences between survivors and controls [22,31,42,49,70,73]. Only three studies (n = 3/19; 16%) found no difference in cognitive functional outcomes pre-to post-chemotherapy or between those who received chemotherapy and the healthy control groups [37,78,81].…”
Section: Studies Examining Cognitive Functional Outcomes Among Cancer...mentioning
confidence: 99%
See 1 more Smart Citation